Local structure and structural properties of vanadium oxide thin films prepared by radio-frequency reactive magnetron sputtering at various oxygen flow rate. Issue 1 (4th December 2021) - Thangdee, Piyaporn; Chongsereecharoen, Ekachai; Chunjaemsri, Thanun; Ekwongsa, Chinawat; Kidkhunthod, Pinit; Chanlek, Narong; Wongdamnern, Natthapong; Manyum, Prapan; Rujirawat, Saroj; Yimnirun, Rattikorn
Abstract: In this work, vanadium oxide thin films were prepared by using radio frequency reactive magnetron sputtering with vanadium metal target. The effect of O2 flow rate was investigated in terms of vanadium oxide thin films by varying O2 /Ar flow rate at 1/20, 2/20, 3/20, 4/20, 5/20, 6/20 (in sccm unit) with fixed RF power at 200 W and sputtering time at 80 minutes. The surface morphology and crystal structure of V2 O5 thin films were investigated by scanning electron microscope (SEM), atomic force microscope (AFM), and X-Ray Diffractometer (XRD) respectively. The influence of the O2 /Ar ratio on a local structure of vanadium oxide thin films was studied by the Synchrotron x-ray absorption spectroscopy (XAS) technique. The oxidation states of vanadium oxide thin films were measured at V K-edge by the x-ray absorption near-edge structure (XANES). The results of XANES spectra at the V K-edge showed that the prepared films under the O2 /Ar flow rate at 1/20 sccm contained the vanadium with the oxidation states of V 3+ and V 5+ while the others contained only V 5+ . This is because the higher O2 /Ar flow rate possibly causes an increase in energy flux at the substrate and the 1s→3d transition peak's intensity, which could lead to a higher deposition rate. To achieve the desired V2 O5 structure, the gas flow rate could be adjusted properly. The evolution of the local structure around V atoms was studied using the extended x-ray absorption fine structure (EXAFS) which supported the XANES results indicating that the structural environment around V atoms is in good agreement with the V2 O5 orthorhombic structure. Finally, XANES and EXAFS fitting results confirmed that the O2 flow rate affected the local structure of vanadium oxide thin films.